3-[(1-Benzyl-1H-1,2,3-triazol-5-yl)methyl]-1,5-dimethyl-1,5-benzodiaze pine-2,4-dione monohydrate - Dardouri, R.; Rodi, Y.K.; Saffon, N.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C21H21N5O2 center dot H2O, the seven-membered ring adopts a boat-shaped conformation with the methine C atom as the prow. In the crystal, the water molecule links adjacent molecules by O-H center dot center dot center dot O and O-H center dot center dot center dot N hydrogen bonds into a zigzag chain running along the c axis of the monoclinic cell.